2019
DOI: 10.15421/021952
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clonal micropropagation on productivity and differentiation of Mentha pіperіta plant tissues

Abstract: Peppermint grass, as a raw medicinal plant material, has great importance for the pharmaceutical industry. The influence of clonal micropropagation and chemotherapy has been established in vitro on six breeds of Ukrainian selection peppermint plants, in particular on the sprouts’ conductive system structure and tissue development, general biomass accumulation, and in vivo productivity of breeds. The influence of clonal micropropagation and chemotherapy on important productivity indices of the plants has been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Peppermint (Mentha piperita L.), is widely used in the cosmetics, pharmaceutical, and food industries [5][6][7][8]. One of its most valuable products is its essential oil (EO) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Peppermint (Mentha piperita L.), is widely used in the cosmetics, pharmaceutical, and food industries [5][6][7][8]. One of its most valuable products is its essential oil (EO) [9].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that earlier studies have already indicated that the use of growth regulators (in particular, BAP) increases the production of EOs and biomass in peppermint [3]. However, as the total EOs yield increases, the application of BAP often affects the production of secondary metabolites such as menthone, menthol, menthofuran, and pulegone [18,22,25,26]. There were no significant differences in the composition of EOs in the control and acclimatized plants.…”
Section: Peppermint's Essential Oil Compositionmentioning
confidence: 73%
“…[16,[20][21][22][23][24]. The use of growth regulators increases the production of EOs by peppermint plants and affects the chemical composition of EOs [18,22,[25][26][27]. The amount of the individual components contained in the EOs changes and undesirable substances are not synthesized, which was confirmed by the experiment of Bertoli et al [20].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation